2014
DOI: 10.1371/journal.pone.0087422
|View full text |Cite
|
Sign up to set email alerts
|

Opportunity or Orientation? Who Uses Urban Parks and Why

Abstract: There is growing recognition that interactions with nature provide many desirable human well-being outcomes, yet increasing urbanization is degrading the quality and quantity of nature experiences. Thus, it has become increasingly important to understand how and why urban dwellers interact with nature. Studies of urban green space use have largely focused on the availability and ease of access to green space, suggesting that greater opportunities to experience such space will lead to increased use. However, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
262
4
10

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 308 publications
(302 citation statements)
references
References 30 publications
26
262
4
10
Order By: Relevance
“…Park characteristics are well known to influence park visitation (Ho et al 2005;Wende et al 2012;Jim and Shan 2013;Zanon et al 2013;Lin et al 2014;Pleson et al 2014), and we found that park size was an important predictor of the relative vegetation cover in visited parks. Furthermore, tree cover and remnant vegetation cover were more important factors in park selection at the local scale than the district or metropolitan park scale.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Park characteristics are well known to influence park visitation (Ho et al 2005;Wende et al 2012;Jim and Shan 2013;Zanon et al 2013;Lin et al 2014;Pleson et al 2014), and we found that park size was an important predictor of the relative vegetation cover in visited parks. Furthermore, tree cover and remnant vegetation cover were more important factors in park selection at the local scale than the district or metropolitan park scale.…”
Section: Discussionsupporting
confidence: 53%
“…A range of social and environmental factors are known to influence park visitation behaviour; this includes gender, age, education and income, which all influence preferences for different types and sizes of parks, as well as the facilities within them (Ho et al 2005;Wende et al 2012;Jim and Shan 2013;Zanon et al 2013;Lin et al 2014;Pleson et al 2014). Research into these human-environment interactions provides important insights into how sustainable landscapes might be designed to deliver recreational ecosystem services (Wu 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Interacting with nature can result in a range of human benefits including physical health, mental health, psychological health, psychological wellbeing, life meaning, cognitive ability and social cohesion, and provide spaces for physical and social activities to take place [3,14,18,19,25,28,[50][51][52][53][54]. Shanahan et al [17] identify three main pathways of nature benefitting wellbeing: direct pathway to physical health (e.g., a tree reflecting light and thereby managing temperature extremes); indirect pathway to physical health (e.g., a tree providing more shade promoting and encouraging physical activity); and an indirect pathway to mental health (e.g., the experience of viewing nature having restorative impacts on the brain).…”
Section: Food Related Wellbeingmentioning
confidence: 99%
“…Currently more than half the human population is living in or close to cities [3,40] and in Australia this is closer to 89% [90]. In low-income countries approximately 28% of the total population lives in cities, however these countries currently have the fastest rates of urban population growth which is putting increasing pressure onto their food systems [43,85,91].…”
Section: Urban Agriculture's Role In Food Securitymentioning
confidence: 99%
See 1 more Smart Citation